The impact of technology on the changing practice of lung SBRT - Aznar, M; Warren, S; Hoogeman, M; Josipovic, M (Elsevier, 2018)
Stereotactic body radiotherapy (SBRT) for lung tumours has been gaining wide acceptance in lung cancer. Here, we review the technological evolution of SBRT delivery in lung cancer, from the first treatments using the stereotactic body frame in the 1990’s to modern developments in image guidance and motion management. Finally, we discuss the impact of current technological approaches on the requirements for quality assurance as well as future technological developments.